Beer, babes, and balls : masculinity and sports talk radio - Nylund, David (SUNY series on sport, culture, and social relations., 2007)
"Beer, Babes, and Balls explores the increasingly popular genre of sports talk radio and how it relates to contemporary ideas of masculinity. Popular culture plays a significant role in fashioning identities, and sports talk radio both reflects and inspires cultural shifts in masculinity. Through analysis of the content of sports talk radio as well as interviews with radio production staff and audience members, scholar and avid sports talk radio listener David Nylund sheds light on certain aspects of contemporary masculinity and recent shifts in gender and sexual politics. He finds that although sports talk radio reproduces many aspects of traditional masculinity, sexism, racism, and heterosexism, there are exceptions in these discourses. For instance, the most popular national host, Jim Rome, is against homophobia and racism in sport, which indicates that the medium may be a place for male sports fans to discuss gender, race, and sexuality in consequential ways. Nylund concludes that sports talk radio creates a male bonding community that has genuine moments of intimacy and connection, signifying the potential for new forms of masculinity to emerge, while simultaneously reproducing traditional forms of masculinity."--Jacket